Legal Reform and Social Equity in Contemporary Society - Sudrajat, Arip Rahman; Urbaningrum, Rexy Nakula (Politeknik Siber Cerdika Internasional, 2025)
Background: Legal reforms play a crucial role in shaping social equity by influencing access to justice, economic opportunities, and the protection of human rights. Historically, legal systems have functioned both as instruments that reinforce structural inequalities and as mechanisms for dismantling them, depending on the design, scope, and implementation of legal reforms. Objective: This study aims to analyze the impact of legal reforms on social equity, with a particular focus on how legislative changes affect marginalized and vulnerable groups within society. Methods: The research adopts a qualitative approach through a systematic literature review and comparative case studies drawn from various jurisdictions. Results: The findings indicate that legal reforms have contributed positively to social equity in areas such as anti-discrimination frameworks, labor rights protection, and criminal justice reform. However, significant challenges remain due to inconsistent enforcement, socio-political resistance, institutional weaknesses, and economic barriers that limit the reach of reforms. The study also finds that legal reforms are more effective when supported by participatory governance, strong accountability mechanisms, and equitable enforcement practices. Conclusion: Legal reforms constitute a vital mechanism for advancing social equity, yet their success depends heavily on robust institutional frameworks and active civic engagement. This study contributes to the broader discourse on law and social justice by identifying best practices for designing and implementing legal reforms that promote equitable outcomes. Future research is recommended to explore the long-term socio-economic impacts of legal reforms across different legal traditions and governance systems.